Curriculum Evaluation of the Textile and Fashion Design Department of Cameroon Opportunities Industrialization Center (COIC), Buea - Yaro, Loveline; Shafak, Tanju Fidel Kottoh (American Journal of Education and Practice, 2024)
Purpose: Although technical and vocational education is a viable solution to unemployment and other socio-economic challenges, there is a dearth of empirical data on the perceptions of various stakeholders. To close this gap, the study proposes a case study evaluation of the program of the Textile and Fashion Design (TFD) department in Cameroon Opportunities Industrialization Center (COIC). Materials and Methods: Tyler's rationale was used as the evaluation framework. The in-depth exploration proceeded in three phases. The first phase was a desk review of relevant documents. The second phase comprised of in-depth interviews with four main groups of respondents: 2 administrators, 3 trainers, 9 trainees, and 6 alumni. For each group of the respondents, an interview guide was used for data collection. The final phase was classroom observation using an observation guide. The data collected was submitted to content analysis, and then reported using both thematic and narrative techniques following the evaluation framework. Findings: The findings show that the TFD department is achieving its overall objective notwithstanding the challenges at the level of the entrepreneurship aspects of the objective. The program is also implemented in ways that enhance the achievement of the objectives, but the gaps in specialization, duration, and resources indicate the need for policy reviews. The assessment policy was found to be consistent with the objectives, and the stakeholder generally perceive the program in a positive light despite the challenges raised. Implications to Theory, Practice and Policy: Recommendations were made to close the identified gaps in the program implementation. For one thing, more needs to be done in digital visibility and sensitization. The challenges faced by the alumni indicate that more needs to be done in achieving the entrepreneurial aspect of the objective. Finally, if the "no entry requirement" policy is maintained, there might be need to consider specialization to increase quality and relevance of the program.